Antarctic network of lamp-calibrated multichannel radiometers for continuous ozone and uv radiation data - Redondas, A.; Torres, C.; Meinander, O.; Lakkala, K.; García, R.; Cuevas, E.; Ochoa, H.; Deferrari, Guillermo Alejandro; Diaz, Susana Beatriz
Three NILU-UV multichannel radiometers have been installed in 1999 at the Argentinian sites of Ushuaia (54S), Marambio (64S) and Belgrano-II (77S) in order to continuously monitor UV radiation, photosynthetically active radiation and total ozone. The measurements were established by INM, Spain in collaboration with FMI, Finland, DNA-IAA, Argentina and CADIC, Argentina to observe and characterize the spatial and temporal evolution of ozone and ultraviolet radiation in the Antarctic region. Special attention has been given to the quality control and quality assurance of the measurements under harsh climatological conditions. The ozone and UV time series of 2000–2006 were calibrated using a polynomial fit for lamp measurements performed every second week all year round. The gaps in these data are minimal, with almost no data missing, and the data products are available from http://www.polarvortex.org in near real time. The data products include the erythemally-weighted UV, UVB and UVA radiation, photosynthetically active radiation (PAR), total ozone (O3) and a cloud parameter (CLT). For UV data, dose rates as well as daily doses are available; from these the maximum measured UV indices (UVI), during 2000–2006, were 12.0, 9.7 and 8.1 at Ushuaia, Marambio and Belgrano-II, respectively. Fil: Redondas, A. Izaña Atmospheric Research Center; España Fil: Torres, C. Izaña Atmospheric Research Center; España Fil: Meinander, O. Finnish Meteorological Institute; Finlandia Fil: Lakkala, K. Finnish Meteorological Institute; Finlandia Fil: García, R. Izaña Atmospheric Research Center; España Fil: Cuevas, E. Izaña Atmospheric Research Center; España Fil: Ochoa, H. Ministerio de Relaciones Exteriores, Comercio Internacional y Culto. Direccion Nacional del Antártico; Argentina Fil: Deferrari, Guillermo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Diaz, Susana Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. ...